Kajian Pemanfaatan Media Massa oleh Aktivis dalam Kampanye Kesetaraan: Kajian Deskriptif Kualitatif Organisasi Perdik di Kota Makassar - Yohanes Lado Tukan; Anil Hukma (Journal of Communication Sciences (JCoS), 2022)
The purpose of this study is to: 1) examine the utilization of mass media by activists with disabilities in liberation campaigns and 2) identify the advantages and disadvantages of using mass media for these activists. The research design used is qualitative descriptive, using the AIDDA theory approach, and the data collected was primary qualitative data through interviews and observations. The results revealed that: 1) PerDIK utilized various forms of mass media in their commemoration campaigns, including internet media such as blogs, YouTube, and online news portals, as well as electronic media like television; 2) the advantages of using mass media in liberation campaigns are that it is effective, creates dynamic images, encourages participation from people with disabilities, reaches a wide range of society including stakeholders, and strengthens movements. However, some disadvantages of using mass media for these campaigns include biased perceptions, potential loss of control, and lack of quality content.